Some Morpho-Functional Changes of the Left Heart in Patients with Viral Liver Cirrhosis - M V. Chistyakova; A. V. Govorin; N. N. Kushnarenko (Рациональная фармакотерапия в кардиологии)
Material and methods. 55 patients with VLC class А, B, C according to Сhild-Pugh were examined. The average age of patients 42 years, disease duration – 3,8 years. Depending on the presence of ascites, patients were divided into 2 groups: 28 patients had no ascites (group 1), 27 patients had ascites (group 2), and a control group of 22 healthy people. Echocardiography was performed by the "VIVID E 95" device. All patients were evaluated diastolic function of the LV in accordance with the АSЕ/ЕAЕ-2009 and ASE/EACVI-2016 recommendations. Holter monitoring of ECG was performed. Statistical data processing was carried out using Statistica 6.0 statistical software package and Mann-Whitney nonparametric test. The correlation analysis was performed using the Spearman coefficient.Results. In all patients there was an increase in the index of myocardial mass and relative wall thickness of LV in comparison with the control group, more severe disorders were identified in patients with VLC with ascites, p<0.001. In the study of LV remodeling, concentric hypertrophy was most common in patients with VLC – in 11 (43%) patients of the 1st group and in 19 (70%) patients of the 2nd group. Holter monitoring of ECG revealed supraventricular extrasystoles in 9 (32%) patients of the 1st group and 11 (40%) – 2nd group; paroxysmal form of atrial fibrillation – in 2 (7%) patients and in 5 (18%), respectively. It was found that the maximum index of the left atrial volume was higher in patients with VLC compared to control, and in patients with ascites this disorder was more pronounced (p<0.001). In accordance with the ASE/EACVI-2016 algorithm, normal diastolic LV function was registered almost twice as often as when using the ASE/EAE-2009 algorithm. Undefined result was recorded in 8% of cases due to tricuspid regurgitation.Conclusion. Thus, patients with VLC develop an increase in the LV myocardial mass with the formation of concentric hypertrophy, remodeling of the left atrium with the occurrence of cardiac arrhythmias, diastolic LV dysfunction, and these changes are more pronounced in patients with ascites. In accordance with the new algorithm ASE/EACVI-2016 for detection of diastolic LV dysfunction, normal LV diastolic function was almost 2 times more common in patients with VLC than in accordance with the old ASE/EAE-2009 algorithm.